Indocyanine green as a near-infrared theranostic agent for ferroptosis and apoptosis-based, photothermal, and photodynamic cancer therapy - Tseng, Hsiang-Ching; Kuo, Chan-Yen; Liao, Wei-Ting; Chou, Te-Sen; Hsiao, Jong-Kai (Frontiers in Molecular Biosciences, 2022)
Ferroptosis is a recently discovered programmed cell death pathway initiated by reactive oxygen species (ROS). Cancer cells can escape ferroptosis, and strategies to promote cancer treatment are crucial. Indocyanine green (ICG) is a near-infrared (NIR) fluorescent molecule used in the imaging of residual tumor removal during surgery. Growing attention has been paid to the anticancer potential of ICG-NIR irradiation by inducing ROS production and theranostic effects. Organic anion transmembrane polypeptide (OATP) 1B3 is responsible for ICG metabolism. Additionally, the overexpression of OATP1B3 has been reported in several cancers. However, whether ICG combined with NIR exposure can cause ferroptosis remains unknown and the concept of treating OATP1B3-expressing cells with ICG-NIR irradiation has not been validated. We then used ICG as a theranostic molecule and an OATP1B3-transfected fibrosarcoma cell line, HT-1080 (HT-1080-OATP1B3), as a cell model. The HT-1080-OATP1B3 cell could promote the uptake of ICG into the cytoplasm. We observed that the HT-1080-OATP1B3 cells treated with ICG and exposed to 808-nm laser irradiation underwent apoptosis, as indicated by a reduction in mitochondrial membrane potential, and upregulation of cleaved Caspase-3 and Bax but downregulation of Bcl-2 expression. Moreover, lipid ROS production and consequent ferroptosis and hyperthermic effect were noted after ICG and laser administration. Finally, in vivo study findings also revealed that ICG with 808-nm laser irradiation has a significant effect on cancer suppression. ICG is a theranostic molecule that exerts synchronous apoptosis, ferroptosis, and hyperthermia effects and thus can be used in cancer treatment. Our findings may facilitate the development of treatment modalities for chemo-resistant cancers.